Observational study on the mitotic rate and other prognostic factors in cutaneous primary melanoma arising from naevi and from melanoma de novo. (14th February 2014) - Betti, R.; Santambrogio, R.; Cerri, A.; Vergani, R.; Moneghini, L.; Menni, S.
Abstract Background Melanomas can arise from naevi or appear de novo. The frequency or the effect of their origin on prognosis is still debated. Mitotic rate (MR) and ulceration of melanomas have been proposed as further new prognostic indexes. Aim To determine the different prognostic factors in melanomas de novo and melanomas from pre‐existing naevi and whether these two melanoma groups have different MR or presence of ulceration. Methods All patients with confirmed primary melanomas observed in our clinic from 1996 to July 2013 were included. The distinction between the two groups of melanomas was histologically based. We compared Breslow's thickness, the number of mitosis/mm2 and the presence of ulceration between the naevus‐associated melanoma and de novo melanoma group. Results Of the 873 melanomas, 626 (71.8%) have a de novo melanoma, 247 (28.2%) a naevus‐associated melanoma. Breslow's thickness was not significantly different in the two groups (0.77 ± 1.47 mm vs. 0.59 ± 1.35 mm). The number of patients with presence of ulceration and MR ≥1 mitosis/mm2 was not significantly different in the two groups (19.6% vs. 16.3%). In thicker melanomas (Breslow's thickness ≥ 1 mm), the number of patients with ≥6 mitosis/mm2 was significantly higher (26.6% vs. 7.9%; P < 0.05) in the de novo melanoma group. Conclusions When mitosis ≥ 1 mm/mm2, the results obtained do not show a better or worse prognosis based on Breslow's thickness, ulceration and MR in melanomas associated with naevus vs. melanomas de novo. When ≥6 mitosis/mm2 are considered, the number of patients in the de novo melanoma group with thick melanoma is highly more represented. The debate about the cut‐off value of mitosis ≥1 mm2 is open.